Assessment on the Social Media Marketing as a Promotional Strategy of Fast- Food Restaurants: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to assess and determine social media marketing as apromotional strategy for fast-food restaurants in terms of entertainment, interaction,trendiness, and customization.The respondents who experienced problems are not far from the number of respondentswho didn’t experience probleMs. The problems that were observed and experienced by therespondents were correlated to the highlighted variables.This study recommended that restaurant operators should consider implementing socialmedia marketing activities to create an atmosphere of trust and credibility that will encouragecustomers to share their experiences with others. Restaurant marketers and operatorsshould strive to create positive online reviews and ratings by encouraging customers toshare their experiences online. The researchers highly recommend that future researchersseek further to improve the whole process and come up with another study to ensure thegratification of customers to the social media marketing strategy of fast-food restaurants.The fast-food restaurants should adopt responses cited by respondents and conduct furtherregular surveys or interviews regarding customers' preferences and suggestions that shouldbe utilized to improve their social media marketing strategies.
Keywords: Business Administration